Assessing the Aquatic Plant Community within the Ross Barnett Reservoir, Mississippi. (June 2014) - Cox, Michael C.; Wersal, Ryan M.; Madsen, John D.; Gerard, Patrick D.; Tagert, Mary L.
Abstract: Alligatorweed, waterhyacinth, and hydrilla are three nonnative aquatic species of concern in the Ross Barnett Reservoir near Jackson, MS. Point-intercept surveys were conducted on the reservoir from 2005 to 2010 to monitor native and nonnative species' distributions and assess herbicide treatment efficacy across the reservoir. Foliar applications of 2, 4-D, glyphosate, imazapyr, and diquat were made during summer months for emergent and free-floating vegetation, whereas submersed applications of liquid copper and granular fluridone were applied in spring and late summer for subsurface hydrilla populations. American lotus is the native species that has been observed the most throughout the survey years, with occurrence frequencies averaging between 17 and 27%. Alligatorweed populations significantly decreased from 21% in 2005 to 4% in 2006; however, they consistently increased in the next 4 yr to 12% occurrence in 2010. Waterhyacinth occurrence has remained relatively constant over the study period, averaging below 10% occurrence. Hydrilla was discovered in the reservoir in late 2005 and has remained below 2% in frequency of occurrence since 2006. Suppression of these nonnative species has been attributed to rigorous monitoring and herbicide applications conducted on the reservoir since 2005. A logistic regression model indicated that as native species richness increased, the likelihood of a nonnative species occurring also increased.